Prognostic value of prognostic nutritional index score and controlling nutritional status score in patients with glioblastoma: A comprehensive meta-analysis - Peng, Jie; Li, Xiaoyu; Huang, Mingsheng; Ma, Mincai; Huang, Qin; Huang, Ning; Cheng, Yuan (Frontiers in Oncology, 2023)
Introduction Several nutritional indicators, including the prognostic nutritional index (PNI) score and the controlling nutritional status (CONUT) score, have been shown to predict the prognosis of patients with glioblastoma. The present meta-analysis was performed to further evaluate the prognostic value of PNI and CONUT scores in patients with glioblastoma. Method The PubMed, EMBASE and Web of Science databases were comprehensively searched for studies that evaluated the ability of PNI and CONUT scores to predict the prognosis of patients with glioblastoma. Hazard ratios (HR) and 95% confidence intervals (CIs) were calculated by univariate and multivariate analyses. Result Ten articles were included in this meta-analysis, involving 1406 patients with glioblastoma. Univariate analyses showed that a high PNI score was predictive of greater overall survival (OS; HR 0.50; 95% CI, 0.43, 0.58; I2 = 0%) and progression free survival (PFS; HR 0.63; 95% CI, 0.50, 0.79; I2 = 0%), whereas a low CONUT score predictive of longer OS (HR 2.39; 95% CI, 1.77, 3.23; I2 = 25%). Multivariate analyses showed that high PNI score (HR 0.64; 95% CI, 0.49, 0.84; I2 = 24%) and low CONUT score (HR 2.79; 95% CI, 2.01, 3.89; I2 = 39%) were independently associated with longer OS, whereas PNI score was not significantly associated with PFS (HR 1.02; 95% CI, 0.65, 1.59; I2 = 0%). Conclusion PNI scores and CONUT scores have prognostic value in patients with glioblastoma. Additional large-scale studies, however, are required to confirm these results.